5.25q-2(3q+1.25)=q+1

Simple and best practice solution for 5.25q-2(3q+1.25)=q+1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5.25q-2(3q+1.25)=q+1 equation:


Simplifying
5.25q + -2(3q + 1.25) = q + 1

Reorder the terms:
5.25q + -2(1.25 + 3q) = q + 1
5.25q + (1.25 * -2 + 3q * -2) = q + 1
5.25q + (-2.5 + -6q) = q + 1

Reorder the terms:
-2.5 + 5.25q + -6q = q + 1

Combine like terms: 5.25q + -6q = -0.75q
-2.5 + -0.75q = q + 1

Reorder the terms:
-2.5 + -0.75q = 1 + q

Solving
-2.5 + -0.75q = 1 + q

Solving for variable 'q'.

Move all terms containing q to the left, all other terms to the right.

Add '-1q' to each side of the equation.
-2.5 + -0.75q + -1q = 1 + q + -1q

Combine like terms: -0.75q + -1q = -1.75q
-2.5 + -1.75q = 1 + q + -1q

Combine like terms: q + -1q = 0
-2.5 + -1.75q = 1 + 0
-2.5 + -1.75q = 1

Add '2.5' to each side of the equation.
-2.5 + 2.5 + -1.75q = 1 + 2.5

Combine like terms: -2.5 + 2.5 = 0.0
0.0 + -1.75q = 1 + 2.5
-1.75q = 1 + 2.5

Combine like terms: 1 + 2.5 = 3.5
-1.75q = 3.5

Divide each side by '-1.75'.
q = -2

Simplifying
q = -2

See similar equations:

| 4s+k=3r | | 9.2s=12.8s-3.96 | | 3y^2=72 | | -20p=-15.58-11.8p | | (9x-5)-(6x-8)= | | 2m+2n+2m+4n+8= | | 7x-5(5x+4)=142 | | 28M+16=4(4M-23) | | 7y^2-49y=0 | | -3=4x+6minusx | | 2n+8+2n+20= | | -n+25+6n+15=-12 | | 7x+5(5+4)=142 | | d(7-x)=4v | | 16+11v=2v-20+6v | | 10x-31+9x-13=127 | | R+300=-214 | | 152-x=138 | | 3(x+y)=8 | | 1.5(4w+1)=2.5w+1 | | -2n-(n-5)=n+1 | | 2x+4x-4=-2x+4 | | (y+2)(y-7)-1=(y+1)(y+3) | | 54=36+x | | -12-18q=-19q | | 14+4k=2+-2k | | 198=3x-5(6x+9) | | 35-6k=7(5-5k) | | 37=7-x | | 29-x=45 | | 18+n=58 | | -7h-5-4h=5-10h |

Equations solver categories